Novel biodegradable stents in the treatment of bronchial stenosis after lung transplantation - Lischke, Robert; Pozniak, Jiri; Vondrys, David; Elliott, Martin J (European journal of cardio-thoracic surgery, 2011)
OBJECTIVE: To evaluate the safety and effectiveness of novel biodegradable (BD) stents to treat bronchial anastomotic stenosis in patients after lung transplantation. METHODS: Twenty BD stents were implanted endoscopically in six patients (median age 41.5 years (range 35-57 years)) with post-transplant bronchial anastomotic stenoses, between 2006 and 2010. All stents were custom-made from bio-absorbable polydioxanone (PDS). The median stent diameter was 12 mm (8-17 mm) and median length was 20mm (12-30 mm). All patients were evaluated clinically, by bronchoscopy and high-definition computed tomography (CT). RESULTS: The stenosis was initially relieved in all cases. There was no bleeding, perforation or displacement after BD stent implantation. Four patients needed multiple stenting for anastomotic re-stenosis. Median time to any re-stenting was 5 months (2-15 months). There was one sudden death, 1 year after the last BD stent implantation, from a pulmonary embolus. All five survivors are in good clinical condition up to 4 years' follow-up (median 40 months, range 7-48 months) since first stenting and intervention-free up to 44 months (median 24 months, range 7-44 months). CONCLUSIONS: This small pilot study shows that BD stents are a safe, effective and reliable alternative to classical metallic stents in patients with anastomotic stenosis after lung transplantation, and may avoid the need for permanent stenting.
Keywords: bronchoskopie; stenty; Bronchial Diseases; anastomóza chirurgická; Humans; lidé středního věku; Airway Obstruction; vstřebatelné implantáty; Lung Transplantation; Anastomosis, Surgical; dospělí; výsledek terapie; lidé; Polydioxanone; Prosthesis Design; Absorbable Implants; stenóza; Adult; Stents; obstrukce dýchacích cest; Middle Aged; Treatment Outcome; polydioxanon; epidemiologické metody; protézy - design; bronchiální nemoci; Epidemiologic Methods; Constriction, Pathologic; Bronchoscopy; transplantace plic